A mad desire to dance : [compact disc, unabridged] : a novel - Wiesel, Elie, 1928-2016 (Random House Audio, 2009)
Doriel, a European New Yorker, turns to Judaism and a psychoanalyst to discover and heal the immense personal wounds he carries. These wounds directly relate to the overabundance of well-detailed memories he carries from the Holocaust and the death of his mother.